Sosialisasi Penggunaan Microsoft Excel Untuk Meningkatkan Keterampilan Pengolahan Data Pada Kader Posyandu Blimbing - Fibia Sentauri Cahyaningrum; Nola Riwibowo; Abdun Nafi Kurniawan; Agus Slamet; Taruna Firlian Tama (Jurnal Insan Pengabdian Indonesia, 2023)
Posyandu (integrated service post) is the government's effort to make it easier for the Indonesian people to obtain maternal and child health services. Skilled posyandu cadres are not only seen from their ability to provide maternal and child health services, but must also be supported by the ability to process administrative data, bearing in mind that in the implementation of posyandu, posyandu cadres are given the task of recording and managing mother and child data. Therefore, this community service program provided socialization on the use of Microsoft Excel to Blimbing posyandu cadres located in Slumbung Village, Gandusari District, Blitar Regency with the aim of improving data processing skills and facilitating reporting of posyandu activity data because manual data processing methods require relatively long time and avoid discrepancies in data processing. The method of implementing this community service activity is the lecture and discussion method. The result of this socialization activity is the increased knowledge and understanding of the cadres of the Blimbing posyandu on the importance of using Microsoft Excel. Furthermore, posyandu cadres need to be given intensive training in using Microsoft Excel.